Profile of tofacitinib citrate and its potential in the treatment of moderate-to-severe chronic plaque psoriasis - Di Lernia V; Bardazzi F (Dove Medical Press, 2016)
V Di Lernia,1 F Bardazzi2 1Dermatology Unit, Arcispedale Santa Maria Nuova IRCCS, Reggio Emilia, 2Division of Dermatology, Department of Experimental, Diagnostic and Specialty Medicine, University of Bologna, Bologna, Italy Abstract: The outlook for patients with psoriasis has improved significantly over the last 10 years with the introduction of targeted therapies. Cytokines exert their effects by activating intracellular signaling and transcription pathways, among which there are Janus kinases (JAKs) and signal transducers and activators of transcription (STAT) pathways. JAKs are intracellular second messengers that are crucial for transmitting extracellular cytokine signals to the cell. JAK inhibition interrupts intracellular signaling and can suppress immune cell activation and inflammation in T-cell-mediated disorders, such as psoriasis. Consequently, JAKs are the subject of intensive research activity, since they represent possible therapeutic targets. Tofacitinib is an orally available compound belonging to a novel category of nonbiologic drugs, the “JAK inhibitors”, which target JAKs. Recently, oral and topical formulations of tofacitinib have been demonstrated to be safe and effective for the treatment of plaque psoriasis in randomized clinical trials. In particular, a 10 mg bid dose of tofacitinib was shown to be noninferior to etanercept 50 mg subcutaneously twice weekly. Questions remain unresolved regarding the safety risk beyond the 5 mg bid dose. This review, assessing the available scientific literature, focuses on the profile of tofacitinib, as investigational compound in the treatment of plaque psoriasis. An overview of the efficacy and safety data from randomized clinical trials is provided. In addition, the authors highlight future potential applications of tofacitinib in other skin diseases, in particular alopecia areata and vitiligo. Keywords: treatment, therapy, systemic, JAKs, vitiligo, alopecia